The FADIR test accuracy for screening cam and pincer morphology in youth ice hockey players - Casartelli, N. C.; Brunner, R.; Maffiuletti, N. A.; Bizzini, M.; Leunig, M.; Pfirrmann, C. W.; Sutter, R. (Journal of Science and Medicine in Sport, 2018)
Objectives: Aim of this study was to evaluate the flexion-adduction-internal rotation (FADIR) test accuracy for screening cam and pincer morphology in youth male ice hockey players without diagnosed hip disorders. Design: Cross-sectional study. Methods: Seventy-four ice hockey players with a mean age of 16 years (range: 13-20 years) were assessed unilaterally. The presence of cam and pincer morphology was evaluated using the FADIR test and magnetic resonance imaging (MRI) (reference standard). Positive FADIR test consisted of groin pain during the maneuver, while positive MRI findings consisted of (1) pure cam, pure pincer or combined morphology and acetabular labral alterations, or (2) pure cam or combined morphology and acetabular labral alterations. Sensitivity, specificity, positive and negative likelihood ratios, and positive and negative predictive values were calculated. Results: For pure cam, pure pincer or combined morphology as positive MRI findings, the FADIR test demonstrated a sensitivity of 41%, specificity of 47%, positive likelihood ratio of 0.78, negative likelihood ratio of 1.24, positive predictive value of 19% and negative predictive value of 73%. For pure cam or combined morphology as positive MRI findings, the FADIR test showed a sensitivity of 60%, specificity of 52%, positive likelihood ratio of 1.24, negative likelihood ratio of 0.78, positive predictive value of 16% and negative predictive value of 89%. Conclusions: The FADIR test is inadequate for screening cam and pincer morphology in youth ice hockey players without diagnosed hip disorders because of the large number of false positive test outcomes.